1988
DOI: 10.1007/bf00418470
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiration in the transition from heavy exercise to rest

Abstract: Transitions from rest to exercise and vice versa are reported to be associated with instantaneous changes in minute ventilation and the changes in the off-transitions are thought to be the reverses of those in the on-transitions. Such changes have been observed mainly in mild-moderate exercise and their extrapolation to heavy exercise above anaerobic threshold is unwarranted. Hence, the purpose of this study was to determine the changes in ventilation in the transition from heavy exercise above anaerobic thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, children and adults may not have similar abilities in shortterm or exhaustive work when corrected for size. 24 It was previously reported that the decline in postexercise hyperventilation is related to the load and duration of the exercise, 25 while it was also found that the recovery time is a function of age. 26,27 Thus it is possible that the duration of post-exercise hyperventilation in younger children is shorter than in older children, leading to earlier release of mediators, followed by earlier bronchoconstriction.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, children and adults may not have similar abilities in shortterm or exhaustive work when corrected for size. 24 It was previously reported that the decline in postexercise hyperventilation is related to the load and duration of the exercise, 25 while it was also found that the recovery time is a function of age. 26,27 Thus it is possible that the duration of post-exercise hyperventilation in younger children is shorter than in older children, leading to earlier release of mediators, followed by earlier bronchoconstriction.…”
Section: Discussionmentioning
confidence: 97%